Intracranial Hemorrhage in the Shadows of Infective Endocarditis as a Silent Menace: A Case Report - Shukor, Ahmad Zulkifli Mohamed; Abidin, Mohd Radhwan; Zainulabid, Ummu Afeera (Bangladesh Journal of Infectious Diseases, 2023)
It is surprising when a patient’s care-taker informed the doctor that their family member could suddenly speak in a different accent. Here we reported a case of a young female with infective endocarditis (IE), who later developed a foreign accent syndrome during her stay in the hospital ward. A plain computed tomography (CT) scan of the brain was performed and it showed a coarse and irregular calcific lesion in the left frontal region. Her condition deteriorated rapidly the next day and she died of intracranial haemorrhage. The haemorrhage was possibly caused by a ruptured mycotic aneurysm, a known complication of IE. Bangladesh Journal of Infectious Diseases, December 2022;9(2):76-79